Interactions between RNA polymerase and the “core recognition element” counteract pausing - Vvedenskaya, Irina O. (Science, 2014)
Transcription elongation is interrupted by sequences that inhibit nucleotide addition and cause RNA polymerase (RNAP) to pause. Here, by use of native-elongating-transcript sequencing (NET-seq) and a variant of NET-seq that enables analysis of mutant RNAP derivatives in merodiploid cells (mNET-seq), we analyze transcriptional pausing genome-wide in vivo in Escherichia coli. We identify a consensus pause-inducing sequence element, G(−10)Y(−1)G(+1) (where −1 corresponds to the position of the RNA 3′ end). We demonstrate that sequence-specific interactions between RNA polymerase core enzyme and a core recognition element (CRE) that stabilize transcription initiation complexes also occur in transcription elongation complexes and facilitate pause read-through by stabilizing RNAP in a post-translocated register. Our findings identify key sequence determinants of transcriptional pausing and establish that RNAP-CRE interactions modulate pausing.